2017
DOI: 10.1111/jbi.13004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphometric data demonstrate alternative consequences of secondary contact inClitarchusstick insects

Abstract: Aim Comparisons of independent secondary contact events provide insights into allopatric speciation. The geographic distribution of Clitarchus stick insects across northern New Zealand corresponds to islands that existed in the Pliocene. Subsequent joining to the mainland provided multiple opportunities for secondary contact. We address the hypothesis that secondary contact has similar effects on parental species, across two peninsulas, due to the simultaneous removal of allopatric barriers. Location Northland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 59 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…These daughters were heterozygous at five or six loci (depending on their father's genotype) where their parents differed. All six genotyped sons were heterozygous at these same loci, with the exception of locus Ch29‐14 (Myers et al, ), where all males genotyped had only the maternal allele observed in the Isles of Scilly, UK population sample. Examination of our genotyping data for 142 individuals indicates that locus Ch29‐14 is sex‐linked.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…These daughters were heterozygous at five or six loci (depending on their father's genotype) where their parents differed. All six genotyped sons were heterozygous at these same loci, with the exception of locus Ch29‐14 (Myers et al, ), where all males genotyped had only the maternal allele observed in the Isles of Scilly, UK population sample. Examination of our genotyping data for 142 individuals indicates that locus Ch29‐14 is sex‐linked.…”
Section: Resultsmentioning
confidence: 92%
“…This insect species has two large metacentric X chromosomes in females, and one X chromosome in males (Morgan‐Richards & Trewick, ). We inferred that one locus (Ch29‐14; Myers et al, ) was sex‐linked, as males always had a single allele. We confirmed that males inherited their mother's allele but not their father's by genotyping sons.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations